Hubungan Antara Penggunaan Kontrasepsi Implan dengan Komunikasi, Informasi, Edukasi (KIE), dan Pengetahuan - Nurul Alfiyah; Djohar Nuswantoro; Sunarsih Sunarsih (Pediomaternal Nursing Journal, 2019)
Introduction: Contraception usage in Indonesia had not effective yet. The high usage of contraception not compensated by evenness on each type of contraception. Implant as a long acting reversible contraception with high effectiveness is rarely used because of negative perception in society. The existence of negative perception caused by lack of information and knowledge about implant contraception. The study analysed association between implant contraception usage with Education Information Communication (EIC) and knowledge.Methods: An observational analytic with a case control design. The population were 822 contraceptive acceptors. Study period on January-December 2018. Total samples were 70 with a sampling technique using purposive sampling. Divided into 2 groups, (35 non-implant acceptors as a case group and 35 implant acceptors as a control group). Data obtained through primary data and obtained from the results of guided interviews and questionnaires. Then analyzed through the chi square statistical test.Results: 60% of acceptors got a good EIC about implant contraception (p=0.001), 51.4% of acceptors had enough knowledge about implant contraception (p=0.94).Conclusion: There is an association between EIC with implant contraception usage, but there isn’t an association between knowledge of implant contraception usage.